Peran Jaminan Sosial dalam Membangun Kesejahteraan Masyarakat Prespektif Maqoshid Syariah: The Role of Social Security in Building Community Welfare from the Perspective of Maqoshid Sharia - Zakariya, A. Fahmi; Nurhayati, Rizka Dwita; Rosida, Ika Nazilatur (Journal of Community Development and Disaster Management, 2025)
Social security plays an important role in building community welfare through four security systems, namely individual, family, community, and state security. In the perspective of Maqashid Syariah, social security aims to protect basic needs (dharuriyat), such as maintaining religion (din), soul (nafs), reason (aql), descendants (nasl), and property (maal), in order to achieve community happiness (falah). This study aims to analyze the role of social security in building community welfare with the Maqashid Syariah approach. The main focus of this study is to describe how the social security system can support the fulfillment of dharuriyat needs for all levels of society.This study uses a qualitative method with a literature study approach. The data used are secondary sources, such as documents, articles, and other supporting literature, which are analyzed descriptively to explore the role of social security based on the principles of Maqashid Syariah. The results of the study indicate that social security from the perspective of Maqashid Syariah can be an important instrument in building community welfare. Support from various parties, including BPJS, government, BAZ, LAZ, UPZ, Muslims, non-Muslims, and poor community groups, is needed to achieve this goal. The Maqashid Syariah approach emphasizes the importance of fulfilling dharuriyat needs as a foundation for just and inclusive social welfare